Oxygen On‐Demand: Understanding the Oxygen Reduction Reaction (ORR) Performance Enhancement of Conductive Polymer Films upon Modification with ZIF‐8 MOF. Issue 24 (28th November 2022) - López, Federico C. D.; Bertoni, Andrés I.; Allegretto, Juan A.; Marmisollé, Waldemar A.; Azzaroni, Omar; Rafti, Matías; Grumelli, Doris
Abstract: Recent developments surrounding the oxygen reduction reaction (ORR) focus on low‐cost alternatives to materials used in traditional electrodes, e. g. Pt. To accumulate competitive advantages, these non‐traditional electrodes often consist of multiple functional coating layers. Considering that each layer can potentially alter the reaction mechanism, thus changing its technological value, it becomes relevant to study how a particular electrode architecture impacts on the considered reaction pathway. From kinetic studies with rotating disk electrodes (RDE) it was found that, for Au electrodes coated with the conductive polymer P(ABA−ANI), either bare or modified with ZIF‐8 (MOF) microcrystals, the ORR occurs (at neutral pH) via an associative pathway, involving a two‐electron transfer process and H2 O2 production. Although ZIF‐8 lacks catalytic activity towards the ORR, its passive role as an in situ O2 reservoir not only enhanced the measured current response, but also extended the region of electrochemical potential under kinetic control. Abstract : The integration of porous materials such as Metal Organic Frameworks (MOFs) and cost‐effective electrocatalysts like conductive polymers into organized electrode nanoarchitectures enables an enhancement of the oxygen reduction reaction (ORR). In this work, we trace back the origin of such effect to the ZIF‐8 MOF phase acting as in‐situ oxygen reservoir through rotating disk electrode (RDE) experiments.